OVERCOMING PHONETIC INTERFERENCE IN LEARNING ENGLISH - Nesterenko, Natalia; Lysenko, Katerina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2024)
The article addresses the issues of linguistic interference in foreign language learning, with a particular focus on phonetic interference. Although this topic is not new—given that throughout human history, territorial conquests and wars have often forced invaders to learn the language of the conquered territories, at least to communicate with the local population—it remains highly relevant. The new language often underwent certain changes, both lexically and phonetically, as a result of these interactions. Similarly, the primary language of the conquerors also evolved under the influence of linguistic contact. The article examines the causes of linguistic and phonetic interference, including factors such as Subconscious Resistance, the so-called "subconscious resistance," Lack of Exposure—insufficient language contact, L1 Influence— the influence of the first language, and Transfer Errors—errors transferred from the native language. The authors propose strategies to address interference-related problems. These include ’Explicit Focus’—paying special attention to problematic articulations, ’Contrastive Analysis’—exercises comparing contrasting sounds, ’Phonetic Drills,’ and ’Immersion’—creating a language-rich environment. ______________ References: • Akulenko, V. (1972). Pytannia internatsionalizatsii slovnykovoho skladu movy: Monohrafiia [Issues of Internationalization of Vocabulary: Monograph]. Kharkiv: Vyd-vo Khark. Un-tu. • Zhluktenko, O. (1974). Deiaki aspekty dvomovnosti: Monohrafiia [Some Aspects of Bilingualism: Monograph]. Kyiv: Vyd-vo Kyivskoho Un-tu. • Shcherba, V. (1974). Do pytannia pro dvomovnist [On the Question of Bilingualism]. In L. V. Shcherba, Movna systema ta movna diialnist [Language System and Language Activity]. Lviv. • Appel, & Muysken, P. (1987). Language contact and bilingualism. London and Baltimore, MD: Edward Arnold. • Celce-Murcia, Brinton, D. M., & Goodwin, J. M. (2010). Teaching pronunciation: A course book and reference guide (2nd ed.). Cambridge, UK: Cambridge University Press. • Crystal, (2008). Dictionary of linguistics and phonetics. London: Blackwell Publishing. • Derwing, M., & Munro, M. J. (2015). Pronunciation fundamentals: Evidence-based perspectives for L2 teaching and research. Amsterdam, Netherlands: John Benjamins Publishing Company. • Gass, M., & Selinker, L. (2008). Second language acquisition: An introductory course (3rd ed.). New York: Routledge. • Hickey, (2010). Language contact: Reconsideration and reassessment. In The Handbook of Language Contact. London: Blackwell Publishing. • Kishe, (2017). Language contact. Paris: DL2A - Buluu Publishing Ghana. • Major, C. (2008). Transfer in second language phonology. In J. G. Hansen Edwards & M. L. Zampini (Eds.), Phonology and second language acquisition (pp. 199–227). Amsterdam, Netherlands: John Benjamins Publishing. • Cook, (2016). Second language learning and language teaching (5th ed.). London, UK: Routledge. • Roach, (2009). English phonetics and phonology: A practical course (4th ed.). Cambridge, UK: Cambridge University Press. • Kenworthy, (1987). Teaching English pronunciation. London, UK: Longman. • Avery, & Ehrlich, S. (2018). Teaching American English pronunciation (2nd ed.). Oxford, UK: Oxford University Press. • Underhill, (2005). Sound foundations: Learning and teaching pronunciation. Oxford, UK: Macmillan Education. • Jenkins, (2000). The phonology of English as an international language: New models, new norms, new goals. Oxford, UK: Oxford University Press.